Evaluasi Faktor-faktor Sosial dan Ekonomi dalam Keputusan Petani Milenial - Sukmawati, Dety; Nataliningsi, Nataliningsi; Kusnadi, Kusnadi (Journal of Innovation in Management, Accounting and Business, 2024)
The aim of this research is to identify the factors influencing the decision of young generations to become millennial farmers in the Cipanas District. This study applies a quantitative verificative associative approach to examine the relationships between variables. Logistic regression method using SPSS 25 software is utilized as a tool to measure and analyze these relationships. The research population consists of millennial farmers and conventional farmers in the Cipanas District during the 2022 planting season, with a total of 120 millennial farmers and 180 conventional farmers. A purposive random sampling method is employed to select a sample of 65 observations. Secondary data is collected through documentation and questionnaires. The research findings reveal that variables such as age, education, knowledge and awareness, land area, capital incentives, marketing incentives, and price guarantees can only explain 64.6% of the decision to become a millennial farmer, while the remaining 35.4% is attributed to unexplored factors. The results also indicate that education, knowledge, and awareness have a positive influence on the decision to become a millennial farmer, while land area does not have a significant impact on this decision. Additionally, age, incentives, mentoring, and price guarantees are found to have a positive influence on the decision to become a millennial farmer.